Exploring Cross-Cultural Influences in the Pakistani Drama Industry: A Critical Analysis (Al-Qamar, 2024)
The aim of this research paper is to highlight the impact of Indian, Turkish, and now Korean content on Pakistani society through television dramas from the last three decades. The study provides a comparative analysis of different global customs, cultural traditions, and lifestyles in our particular local drama, perceiving how our drama industry has evolved with foreign influences over time. While keeping in mind our glorious era of the 1970s, 80s, even 90s, and millennium, Pakistani modern-day drama has been overshadowed by foreign supremacy. The overlapping similarities among these cultures are one of the reasons the audiences can relate to these drama genres and conclusively are fascinated with their influence. Although it is a matter of consideration that our local viewer has a wide variety of drama content on other platforms, the growing popularity and impact of the abovementioned cultures can be relatable to modern-day collective issues. Moreover, the present study proves that the influence of Indian, Turkish, and Korean content in our local drama industry is gradually changing the lifestyles and mindsets of youth. Undoubtedly, international content shares some relevance rather than fascination and may promote cultural diversity, but the fastest-changing trends among Pakistani youth require attention and an immediate approach to redefining cultural identity. Moreover, the study reveals that our local drama become more commercialized while addressing serious social issues due to foreign influences, which are not alienated but irrelevant to Indigenous Pakistani society. This comparative analysis has been done on the basis of the viewer’s perception and exploratory research method towards foreign influences in our local drama industry using the technique of innate expressionism.
Keywords: Drama; Cultural Identity; Foreign influences; youth